2009
DOI: 10.1007/s00432-009-0745-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of Bmi-1 oncoprotein is associated with progression and prognosis in colon cancer

Abstract: We have shown that expression of Bmi-1 was elevated in colon cancer and might serve as an independent prognostic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 27 publications
(23 reference statements)
6
88
2
Order By: Relevance
“…Bmi1 mRNA and protein overexpression were previously demonstrated in CRC tumor (5,7) and were positively correlated with tumor stage, invasion and metastasis (6), as well as with poor disease-free and overall survival (6,19), suggesting that Bmi1 is a promising prognostic biomarker in CRC patients. To the best of our knowledge, this study was the first to further demonstrate that the changes in plasma Bmi1 mRNA level prior to and following resection of the primary tumor was prognostic for the development of metastasis, indicating the potential of circulating Bmi1 mRNA levels as a non-invasive, convenient and relatively cost-effective surrogate biomarker for the management of postoperative CRC patients and possibly patients with other types of cancer in which Bmi1 is also overexpressed.…”
Section: Discussionmentioning
confidence: 71%
“…Bmi1 mRNA and protein overexpression were previously demonstrated in CRC tumor (5,7) and were positively correlated with tumor stage, invasion and metastasis (6), as well as with poor disease-free and overall survival (6,19), suggesting that Bmi1 is a promising prognostic biomarker in CRC patients. To the best of our knowledge, this study was the first to further demonstrate that the changes in plasma Bmi1 mRNA level prior to and following resection of the primary tumor was prognostic for the development of metastasis, indicating the potential of circulating Bmi1 mRNA levels as a non-invasive, convenient and relatively cost-effective surrogate biomarker for the management of postoperative CRC patients and possibly patients with other types of cancer in which Bmi1 is also overexpressed.…”
Section: Discussionmentioning
confidence: 71%
“…On the day of measuring the growth rate of untreated and transfected cells (24,48,72 and 96 h, respectively), 100 μl of spent medium was replaced with an equal volume of fresh medium containing 10% CCK-8, then cells were continued to incubate at 37˚C for 3 h, and the absorbance was finally determined at 450 nm using Microplate reader.…”
Section: Methodsmentioning
confidence: 99%
“…The p53 pathway is usually inactivated by TP53 mutation, amplification of MDM2 or p14ARF deletion in a number of human cancers (37,38). Previous studies have demonstrated that Bmi-1 is a potent repressor of the p14ARF-MDM2-p53 pathway (13,39,40). Inactivation of the p53 pathway by Bmi-1 has been identified in lymphomagenesis and oncogenesis in human non-small cell lung cancer (15,37,41).…”
Section: Decreased Expression Normal Expression Overexpression ------mentioning
confidence: 99%
“…As a transcriptional repressor through chromatin modification, Bmi-1 is involved in axial patterning, cell cycle regulation, hematopoiesis and senescence (7,8). Overexpression of Bmi-1 has been observed in a variety of human cancers, including gastric (9), breast (10), colorectal (11) and head and neck cancers (12), and it was also observed that expression of Bmi-1 is associated with the development of tumors (13,14). It was reported that overexpression of Bmi-1 in primary human cancer cells may cause downregulation of the INK4a-ARF locus and affect the pathway of p14ARF-Mdm2-p53 (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation